Prediksi Jumlah Siswa Baru Menggunakan Least Square Method - Aspriyani, Riski; Ahmad, Mizan (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2023)
In the process of admitting new students, each school has a different strategy to increase the number of applicants and the number of students accepted. The publication strategy is structured to achieve the expected goals or to get the number of students according to the quota. The publication strategy will work well if the school has predictive data on the number of students that will come. Therefore, researchers do research with the purpose to predict the number of new students at SMA Ya Bakii 1 Kesugihan using the Trend Linear model with the Least Square to the number of new students from 2002/2003 to 2022/2023. The results of the analysis show that the Least Square Method prediction model in the form of y =49.424+4.463x gives accurate or good results with a MAPE value of 11.996%. While the prediction results for the next five years, namely 2023/2024, 2024/2025, 2025/2026, 2027/2028, and 2029/2030 are 148 students, 152 students, 157 students, 161 students, and 165 students.